Geriatric Population During the COVID-19 Pandemic: Problems, Considerations, Exigencies, and Beyond - Kuldeep Dhama; Shailesh Kumar Patel; Rakesh Kumar; Jigyasa Rana; Mohd. Iqbal Yatoo; Akshay Kumar; Ruchi Tiwari; Jaideep Dhama; Senthilkumar Natesan; Rajendra Singh; Harapan Harapan; Harapan Harapan; et al. (Frontiers Media S.A., 2020)
The coronavirus disease 2019 (COVID-19) pandemic wreaked havoc worldwide, with more than 20 million confirmed cases and nearly 0. 75 million deaths as of 10th August 2020. Various factors determine the severity and symptoms of this infection. Older age and underlying diseases are the challenges being faced in controlling and treating COVID-19. In 2019, 703 million of the global population was older than 65 years of age. The estimated mortality due to COVID-19 in people older than 76 years of age is reportedly 18%. Frequent infections in older people, higher disease severity, and increased mortality are major challenges in the implementation of appropriate preventive measures and future strategies to protect against this disease in geriatric population. Poor health status, weak immune function, lowered organ function, increased probability of multiple underlying diseases, and poor attention to personal health can increase the susceptibility to various diseases in the geriatric population. Concerning inadequate immunity, the decrease expression of receptors and exaggerated pathophysiologic responses can be debilitating. However, future studies will reveal the hidden facets in these aspects in this COVID-19 catastrophe. In this article, we reviewed the main concerns of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the geriatric population, including the risk of acquiring severe COVID-19 resulting in mortality, variation in clinical manifestations, and other pandemic-related concerns. We also discussed the need for increasing attention toward the elderly, taking appropriate prevention and control measures, and considering geriatric-related adjustments in vaccine design and development.